Human interaction theory for sustainable city / Dasimah Omar, Nik Hanita Nik Mohamad and Filzani Illia Ibrahim - Omar, Dasimah; Nik Mohamad, Nik Hanita; Ibrahim, Filzani Illia
In relation to open spaces, Malaysia has received very little attention from researchers, unlike the West, where many studies have explored how human needs are fulfilled by urban parks and open spaces. It is strongly believed that aspects such as amount of public green open spaces per inhabitant, public parks, and recreation areas are often mentioned as important factors to make the city liveable, pleasant and attractive for its citizens. Developing more sustainable cities is not just about improving the biotic aspects of urban life, but it is also about the social aspects of city live which then include peoples' satisfaction, experiences and perceptions of the quality of their everyday environments. However, it can be argued that the total public green open spaces allocated at one area does not mean anything if the green area is qpt being fully utilized and used by the people from the surrounding areas. The provided area will be more beneficial and sustainable if the urban dwellers make full use of the open spaces itself. This research is undertaken to fill this ' knowledge gap. It is vital to study the human interactions towards green open spaces or parks which will then promote sustainability of the city. It would then help to identify the perceived benefits that urban dwellers get from the physical, social and natural interactions towards the green open spaces. Thus, it Will then help to identify the level of sustainability of the city and at the same time improve the indicators in The Malaysian Urban Indicators Network (MURNInet).